1970
DOI: 10.1111/j.1432-1033.1970.tb00927.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the 2′OH Group upon the Binding of Nucleotides by Basic Polyamino Acids

Abstract: The position of the phosphate group on the ribose of nucleoside monophosphates markedly influences their binding behavior with basic polyamino acids, such as poly-L-lysine and poly-1;-arginine. Equilibrium dialysis of adenine and guanine derivatives has revealed that the binding of 5'-and 3'-ribonucleotides (group I, possessing a free 2'OH group) to basic polyamino acids is clearly different from that of 2'-rib0 and 5'-deoxyribonucleotides (group 11, the 2'OH group is blocked and absent, respect.). At low nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1970
1970
1975
1975

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…These results, together with those already mentioned, make it clear that the association of the nucleotides with the basic polyamino acids consists of a primary electrostatic attraction, without which the interaction does not take place, and a secondary one, the or 5 X The cooperative nature of these interactions at high nucleotide concentrations has been treated in detail (14,18).…”
Section: -mentioning
confidence: 85%
See 3 more Smart Citations
“…These results, together with those already mentioned, make it clear that the association of the nucleotides with the basic polyamino acids consists of a primary electrostatic attraction, without which the interaction does not take place, and a secondary one, the or 5 X The cooperative nature of these interactions at high nucleotide concentrations has been treated in detail (14,18).…”
Section: -mentioning
confidence: 85%
“…Several studies (18,19) examined the importance of the 2'-OH group. Circular dichroic spectra showed that guanosine 5'-monophosphate and guanosine 3'-monophosphate (with 2'-OH groups) both caused changes in the spectra of poly-L-lysine a t short wavelengths, indicating polyamino acid conformational change, and at high wavelengths, indicating association of the bases.…”
Section: -mentioning
confidence: 99%
See 2 more Smart Citations